Sur le façonnement international des causes liées à la sexualité - Broqua C.; Fillieule O.; Roca I Escoda M. (Critique Internationale, 2016)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; droit; europe; histoire et politique; identités LGBTQIA2+; occident; premier cycle; périodes historiques; queer; régions géographiques; science politique et droit; sexualité; shm4000; systèmes d'oppressions; thématiques

Moving politics: Emotion and ACT UP’s fight against AIDS - Gould, Deborah B. (University of Chicago Press, 2009)
In the late 1980s, after a decade spent engaged in more routine interest-group politics, thousands of lesbians and gay men responded to the AIDS crisis by defiantly and dramatically taking to the streets. But by the early 1990s, the organization they founded, ACT UP, was no more—even as the AIDS epidemic raged on. Weaving together interviews with activists, extensive research, and reflections on the author’s time as a member of the organization, Moving Politics is the first book to chronicle the rise and fall of ACT UP, highlighting a key factor in its trajectory: emotion. Surprisingly overlooked by many scholars of social movements, emotion, Gould argues, plays a fundamental role in political activism. From anger to hope, pride to shame, and solidarity to despair, feelings played a significant part in ACT UP’s provocative style of protest, which included raucous demonstrations, die-ins, and other kinds of street theater. Detailing the movement’s public triumphs and private setbacks, Moving Politics is the definitive account of ACT UP’s origin, development, and decline as well as a searching look at the role of emotion in contentious politics.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amériques; discipline; identités LGBTQIA2+; militance; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions; états-unis